The Extent Of Compliance With The Aaoifi Accounting Standards By Islamic Banks In Bahrain And Malaysia - Adel Mohammed Yaslam Sarea
The accounting and auditing organization for Islamic financial institutions (AAOIFI) had taken a proper initiative to develop accounting, auditing, governance and ethics standards for Islamic Financial Institutions (IFIs). The AAOIFI standards serve as a guideline that may reflect the unique characteristics of IFIs and become a useful tool to meet the various needs of IFIs. Currently, one the major challenges facing Islamic Financial Institution (IFS) lies in the preparation of the financial statements under different accounting standards and which may result to problem of comparability, reliability and compliance level’s measurement. This has however resulted to a heated debate among scholars which has hitherto translated to the evolving existing literature surrounding the interpretation of the level of compliance with the AAOIFI accounting standards. This study therefore mainly investigates the level of compliance with the AAOIFI accounting standards by Islamic banks in Bahrain and Malaysia and thus provides answers to the current debate. The basis of the study was diffusion of innovation theory which states that, the perceived relative advantage, compatibility, complexity, trialability and observability influence the level of compliance or adoption. The investigation is however undertaken by employing a survey method which involved questionnaire as primary data and annual reports as secondary data. The data was later analyzed using descriptive statistics, regression analyses and t–test. The t-test was conducted to verify the mean differences among the respondents in Islamic banks. The finding of the study therefore indicates that, sample mean of banks in Bahrain is slightly higher in term of compliance with the AAOIFI accounting standards compared to Malaysia. Even though such difference is not so significance based on the fact that, β > 0.05. Moreover, the results revealed that, although the AAOIFI accounting standards are not mandatory in Malaysia, there are some similarities between the perceptions of Islamic banks in Malaysia and Bahrain on certain aspects related to the responsibility to comply with the AAOIFI accounting standards. The findings from the current study therefore contribute towards a better understanding and acceptability of the AAOIFI accounting standards.